Challenges encountered by novice divers in their initial four open water dives of certification programs - Kukuh Pambuka Putra; Bonifacius Arbanto; Angkit Kinasih; Muchamad Arif Al Ardha (Journal Of Sport Education (JOPE), 2023)
(English)To achieve an Open Water Diver (OWD) license, a diver is required to complete a minimum of four open water dives, which are typically carried out during the certification exam for open water diving. These initial dives are known to present challenges and difficulties for divers. The present study aims to identify the specific issues that arise during the first four open water dives in the training and certification of Open Water Divers. A total of ten participants who had undergone OWD certification training between September 2-5, 2022, in Karimunjawa waters, were selected to participate in the study. The participants consisted of three male and seven female divers, aged between 19-23 years old. The study identified a range of challenges experienced by the participants, including five physiological issues, seven equipment-related technical problems, and thirteen issues related to material mastery. Almost all participants reported encountering some form of difficulty during their first four open water dives. However, the severity of these issues was generally mild, and they did not significantly impede the diving process. The findings of this study suggest that novice divers are likely to encounter difficulties during their initial open water dives. Nevertheless, these issues can be addressed through experience and training. The study highlights the importance of developing strategies and interventions that aim to reduce the occurrence of these issues and enhance the overall safety and effectiveness of open water diving certification programs(Indonesian)Penelitian ini bertujuan untuk mengidentifikasi permasalahan spesifik yang muncul selama empat penyelaman perairan terbuka pertama dalam pelatihan dan sertifikasi Penyelam Perairan Terbuka. Sebanyak sepuluh peserta yang telah menjalani pelatihan sertifikasi OWD pada tanggal 2-5 September 2022 di perairan Karimunjawa dipilih untuk mengikuti penelitian. Pesertanya terdiri dari tiga penyelam laki-laki dan tujuh penyelam perempuan, berusia antara 19-23 tahun. Studi ini mengidentifikasi berbagai tantangan yang dialami oleh para peserta, termasuk lima masalah fisiologis, tujuh masalah teknis terkait peralatan, dan tiga belas masalah terkait penguasaan materi. Hampir semua peserta melaporkan mengalami beberapa kesulitan selama empat penyelaman perairan terbuka pertama mereka. Namun, tingkat keparahan masalah ini umumnya ringan, dan tidak menghambat proses penyelaman secara signifikan. Temuan penelitian ini menunjukkan bahwa penyelam pemula kemungkinan besar akan menghadapi kesulitan selama penyelaman awal di perairan terbuka. Namun permasalahan ini dapat diatasi melalui pengalaman dan pelatihan. Studi ini menyoroti pentingnya mengembangkan strategi dan intervensi yang bertujuan untuk mengurangi terjadinya masalah-masalah ini dan meningkatkan keselamatan dan efektivitas program sertifikasi penyelaman perairan terbuka secara keseluruhanCopyright © The Author (s) 2023Journal of Sport Education (JOPE) is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.